Aktivitas E.coli dan Stapphylococcus terhadap Penambahan Lactobacillus dari Rebung Asam - Welkriana, Putri Widelia; Halimatussa'diah, Halimatussa'diah (Persatuan Dosen Kesehatan Masyarakat, 2023)
Lactic acid bacteria produce antimicrobial protein compounds. This compound can inhibit the development of gram-positive and negative bacteria. However, this compound is not harmful to intestinal microflora and is easily digested by enzymes in the digestive tract. This protein compound comes from fermented food products and other processed food products, one of which is sour bamboo shoots with a fermentation time of 7 days. In sour bamboo shoots, Lactobacillus sp. was found. with pure strains of FNCC 0027 and C410LI genes. This is the result of previous research. Tamarind bamboo shoots are one of the processed products found in Bengkulu province. This research aims to determine the optimal conditions for the compounds produced by these bacteria. The methods used include: BAL cultured, BAL confirmed, antibacterial BAL isolated, E. coli and Staphylococcus activity test, antibacterial test for proteolytic enzymes, and temperature and pH measurements. The results of the research showed that the effectiveness of E. coli activity was 65.5% and S. aureus was 21% after the two bacteria were given the addition of Lactobacillus brevis strain 2096 16S ribosomal RNA gene. At varying temperatures, the inhibition zone activity of the two bacteria was highest at 1000C, while the activity of the inhibition zone was highest at pH 6.